Development of Double Mini Windmill with Smart Monitoring System - Hairani, Muhammad Faiz; Jumaat, Siti Amely (Journal of Electronic Voltage and Application, 2022)
Nowadays, renewable energy is becoming the most reliable way to generate electricity in exchange with non-renewable energy which commonly comes from coals and gases. This project is about development of double mini windmill with smart monitoring system. Thus, the project addresses the development of mini wind energy with monitoring system by using Arduino UNO as main microcontroller. For the project development, the voltage and current sensors are used to monitor the mini wind energy system’s performance. The data logging shield board was used to allow the data collection system save in the micro-SD card. Data logger is a platform used to represent the data collection into Microsoft excel. Double mini windmill energy data collection was conducted to assess the wind energy performance through reading the data from the LCD of the monitoring system. The maximum power generated is 3.632W with 6.0m/s wind speed while the minimum power generated is 0.362W with 2.4m/s wind speed. The project was tested at Pantai Punggor, Batu Pahat, Johor on 9 June 2022 and 10 June 2022 while at the residential area Taman Universiti, Parit Raja, Batu Pahat, Johor the project implemented on 11 June 2022.